Technological features of the method of liquid-phase epitaxy when growing InP/GaInAsP heterostructures - Mikhail G. Vasil’ev; Anton M. Vasil’ev; Alexander D. Izotov; Yuriy O. Kostin; Alexey A. Shelyakin (Конденсированные среды и межфазные границы, 2021)
Semiconductor devices of quantum electronics based on InP/GaInAsP heterostructures require the creation of non-defective chips for emitting devices and photodetectors. The production of such chips is impossible without a thorough technological study of the growth processes of epitaxial structures. One of the important problems in relation to the growth of such structures is the growth defects associated with the process of dissociation of indium phosphide on the surface during their growth. The aim of the work was the investigation of the process and mechanism of destruction (dissociation) of the surface of indium phosphide substrates in the range of growth temperatures of structures, as well as the study of methods and techniques that allow minimize the process of dissociation of surface of indium phosphide. The work provides studies of the growth processes of InP/GaInAsP heterostructures, from the liquid phase, taking into account the degradation processes of the growth surface and the mechanisms for the formation of dissociation defects. The schemes of the dissociation process of the InP on the surface of the substrate and the formation of the defective surface of the substrate were analysed. At the same time, technological methods allowing to minimize the dissociation of the surface compound during the process of liquid-phase epitaxy were shown. The original design of a graphite cassette allowing to minimize the dissociation of the indium phosphide substrate in the process of liquid-phase epitaxy was proposed